A SOCIETY OF THE POSTABUNDANCE, FROM THE CONSUMPTION’S REDUCTION TO THE GROWTH OF THE SPIRITU AL SATISFACTION - MIRELA CRISTIANA NILA STRATONE (Challenges of the Knowledge Society)
One close-up view of the consumption reduction on global scales involves beyond the economy reasons analysis, a analysis of the causes and sociological effects of this phenomenon too, in view of the invitation of some concrete and general directions of the necessary at his real value. In view to the reach of the proposed aim there have been followed as aims: the presentation of some initiatives already in existence but inadequate to the definition of spiritual and material needs; the prominence of the needs of the individuals to preponderant reinvest in the spiritual needs satisfaction and in the material satisfaction restriction at the basic needs; the promotion of the mainstream of the consumption reduction; the redefinition of the simplicity in combination with the markers which are substituting symbolical the opulence. The aim of this paper consist in the testing to sustain the move centred on the so-called voluntary simplicity, in the view of the global society reorientation to the abnegation of the material accretion to the benefit of the environment conservation on a side, and on the other side in the view of the spiritual life enrichment of the individuals, which will get on a form of a post abundance society.